'In considerable variety' introducing the diversity of Australia's insects - New, Tim R.; SpringerLink (Online service). (Netherlands Springer, 2011)
Many conservationr managers lack entomological training and the perspective needed to conserve insects within their areas of responsibility. Using Australian insect examples this book provides an introduction to basic entomology and emphasises the massive taxonomic, ecological and evolutionary diversity within this fauna, together with its interactions with humanity.  It is written largely in non-technical language, to provide accessible information on many aspects of insect natural history and the importance of their diversity and conservation, and contains suggestions for further reading to expand on the themes introduced.
Preface -- Chapter 1. The basic insect pattern: theme and variations -- Chapter 2. Fossils and major insect adaptations -- Chapter 3. Insect life histories -- Chapter 4. Origins, distributions and diversity -- Chapter 5. Environments and habitats for insects in Australia -- Chapter 6. Foods and feeding biology -- Chapter 7. Insect behaviour and lifestyles -- Chapter 8. Insect communities -- Chapter 9. Insect populations -- Chapter 10. Insects in inland water environments -- Chapter 11. Australia's alpine insects -- Chapter 12. Lowland insects and their environments: non-forest insects -- Chapter 13. Forest insects -- Chapter 14. Insects and people in Australia -- Chapter 15. Australia's alien insects -- Chapter 16. Conservation -- Chapter 17. Diversity and its implications for understanding Australia's insects -- Appendix 1. Australia's insects: the players -- Index.
Electronic reproduction.
Keywords: Insects -- Variation -- Australia; Insects -- Australia; Biodiversity -- Australia; Electronic books